2019
DOI: 10.1002/14651858.cd008618.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for improving outcomes after osteoporotic vertebral fracture

Abstract: Background-Vertebral fractures are associated with increased morbidity (e.g., pain, reduced quality of life), and mortality. Therapeutic exercise is a non-pharmacologic conservative treatment that is often recommended for patients with vertebral fractures to reduce pain and restore functional movement. Objectives-Our objectives were to evaluate the benefits and harms of exercise interventions of four weeks or greater (alone or as part of a physical therapy intervention) versus non-exercise/nonactive physical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 76 publications
4
63
2
1
Order By: Relevance
“…In addition, exercise can help to achieve beneficial and significant effects on quality of life, balance, and functional mobility also in patients with osteoporosis-related vertebral fractures (43,44). However, there is still no agreement on which type of exercise, in terms of intensity, frequency, duration, type and setting, is optimal and can affect bone metabolism in people with osteoporosis (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exercise can help to achieve beneficial and significant effects on quality of life, balance, and functional mobility also in patients with osteoporosis-related vertebral fractures (43,44). However, there is still no agreement on which type of exercise, in terms of intensity, frequency, duration, type and setting, is optimal and can affect bone metabolism in people with osteoporosis (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals with vertebral fractures require exercise that is tailored to address safety and related impairments [ 13 ]. A recently updated systematic review on the effect of exercise for people with vertebral fracture [ 14 ] concluded that there is moderate-quality evidence that exercise improves physical performance. However, few studies have evaluated whether the effects of exercise are sustained after the intervention has ceased [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…W literaturze światowej nie mamy wystarczających dowodów, aby określić jednoznaczny wpływ ćwiczeń fizycznych na złamania lub zranienia. Wyniki nie przedstawiają klinicznie znaczącej poprawy i należy je interpretować ostrożnie ze względu na niską jakość dowodów z powodu niespójnych wyników i ograniczeń badań [6].…”
Section: Wykres 7 Najczęściej Wykonywana Przez Pacientów Czynność W unclassified